1999
DOI: 10.1177/014920639902500402
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Test of a Model of the Work-Family Interface

Abstract: Recent efforts to more fully understand the mechanisms through which work and family experiences and their cross-over effects influence well-being have stimulated the development of integrative models of the work-family interface. This line of research is represented by the model which Frone, Russell, and Cooper (1992) tested with a sample of U.S. employees. In the current study, we examine the cross-cultural generalizability of this model among married Hong Kong employees. Results of the analyses suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
183
2
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(210 citation statements)
references
References 46 publications
(92 reference statements)
15
183
2
10
Order By: Relevance
“…By contrast, when work stress interferes after office time, it can impair employees' well-being. Because Chinese culture tends to value family over society, Chinese managers tend to consider that work responsibilities interfere with family responsibilities, whereas American managers are more likely to complain that family interferes with work responsibilities (Aryee, Fields, & Luk, 1999;Spector et al, 2007). Prior research suggests that Western cultures prefer a strict separation between work and non-work activities, whereas Eastern cultures tend to blur the boundary between work and non-work activities (Liu & Almor, 2016;Uhlmann, Heaphy, Ashford, Zhu, & Sanchez-Burks, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, when work stress interferes after office time, it can impair employees' well-being. Because Chinese culture tends to value family over society, Chinese managers tend to consider that work responsibilities interfere with family responsibilities, whereas American managers are more likely to complain that family interferes with work responsibilities (Aryee, Fields, & Luk, 1999;Spector et al, 2007). Prior research suggests that Western cultures prefer a strict separation between work and non-work activities, whereas Eastern cultures tend to blur the boundary between work and non-work activities (Liu & Almor, 2016;Uhlmann, Heaphy, Ashford, Zhu, & Sanchez-Burks, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that both WIF and FIW are not significant influence employee's job satisfaction in both state-owned enterprises (SOEs) and foreign-invested companies (FIEs).This finding is consistent with Lu et al (2010) study that found that "WIF may have a less damaging effect on collectivists due to their less rigid demarcation of the work/family boundary and greater tolerance of spill over between the two life domains". As the job is considered as a way to carry out family duties in collectivists (Aryee et al, 1999), working long hours or bring work tasks at home are accepted when these activities contribute to family welfare.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not have adequate measures of work outcomes to make such an analysis. A few studies have found that family-to-work conflict mediates relationships between a limited range of family demands and work outcomes (Aryee, Fields, & Luk, 1999;Frone, Russell, & Cooper, 1992;Frone et al, 1997; but see Grandey & Cropanzano, 1999). Additional work is needed to examine the mediating effects of familyto-work conflict with a broader range of demands and work outcomes.…”
Section: Discussionmentioning
confidence: 99%